EOSINOPHILIC PUSTULAR FOLLICULITIS OF INFANCY - Klara Cvenkel; Mateja Starbek Zorko (The Society for Children with Metabolic Disorders, 2021)
Eosinophilic pustular folliculitis of infancy (EPFI) is a rare, idiopathic, recurrent, self-limiting skin disease. It presents as papulopustules and folliculitis with eosinophilic inﬁltrates. The lesions are usually located on the scalp but also on other parts of the head, neck, trunk, or extremities. Most often it occurs in the ﬁrst months of life and proceeds without signs of systemic illness. EPFI usually resolves spontaneously within a few months to years and is often unrecognised by physicians and consequently overtreated.